Understanding the Coach-Coachee-Client relationship: A conceptual framework for executive coaching - Correia, Mara (2017)
Objectives: There is a need for a more comprehensive understanding of how coaching processes psychologically operate. This paper presents the findings from a study aimed to characterise the coaching process experience and to identify how specific experiences contribute to coaching outcomes. Design: A qualitative design was adopted. Data was analysed by Interpretative Phenomenological Analysis (Smith, 2008). Method: Data was collected from 10 participants, this included coaches (N=4), coachees (N=5) and one commissioner, three times along the coaching process. A total of 30 interviews were undertaken. Findings: Coaching outcomes can be generated by three essential mechanisms: Projection of Future Self; Perspectivation of Present Self; and Confirmation of Past/Present Self. Each mechanism’s name represents a particular effect on coachee’s self and may evolve diverse coaching behaviours. Although they all can be actively managed to generate sustainability of outcomes, each mechanism tends to contribute differently to that sustainability. Conclusion: The study provides a comprehensive understanding of the different methodological and experiential ingredients of the coaching process and its implications. While most coaching research is focused on identifying coaching results based on a retrospective analysis, this is one of the first studies accompanying longitudinally the coaching process and capturing an integrative understanding of its dynamics. Moreover, the study provides evidence of how coaching can differently deliver sustainable outcomes and be used as a valuable developmental tool in organisations. The study contributes to our understanding of theory building and raises questions for further research on the uniqueness of coaching interventions.